Tire wear particles in the marine environment: sources, migration, ecological risk and control strategy - Wang, Yanzhe; Xu, Jie; Zhao, Yunfeng; Pan, Ying; Zhang, Zaiwang; Liu, Suzhe; Chen, Xiaohui; Zhang, Jiqiang; Wu, Tao (Frontiers in Marine Science, 2025)
With the global proliferation of vehicular transportation, tire wear particles (TWPs) have emerged as a pervasive class of emerging contaminants in the environment. Primarily originating from terrestrial road networks, these anthropogenic particulates undergo complex environmental transport through atmospheric deposition and hydrological processes, ultimately accumulating in marine compartments through seawater column retention, benthic sedimentation, and bioaccumulation within marine trophic webs. The environmental impacts of TWPs manifest through multiple mechanisms including physically effects on marine organisms, chemically leaching of toxic tire components, and ecologically bioaccumulation and biomagnification. Current research priorities emphasize the development of standardized monitoring protocols for TWPs quantification and the implementation of source control strategies through green material engineering. This review systematically examines the environmental fate, ecological impacts, and risk mitigation approaches associated with marine TWPs pollution, providing critical insights for developing evidence-based management frameworks.